PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN PRODUK BERAS LOKAL DI PASAR TRADISIONAL KECAMATAN PENAJAM KABUPATEN PENAJAM PASER UTARA - Trihaksami, Anugrahita Melinia (Jurnal Magrobis, 2018)
This research is conducted to know the effect of marketing mix to consumer decision in buying of local rice product at traditional market of Penajam Sub-district of North Penajam Paser. Methods of data collection in this study was conducted by Observation, Questionnaire and Interview or interview located at the Traditional Market District Penajam North Penajam Paser Regency. Based on the results of data analysis, F test results show that product (X1), price (X2), promotion (X3) and distribution (X4) simultaneously significantly influence the decision of purchasing local rice in Traditional Market of Penajam Sub-district of North Penajam Paser Regency. The result of t test shows that the price (X2) and the distribution (X4) have a significant effect on the local rice purchase decision. While product (X1) and promotion (X4) have an insignificant effect to decision of purchasing of local rice in Traditional Market of Penajam Sub-Province of Penajam Paser Utara Regency. The contribution of marketing mix factor to local rice purchasing decision in Penajam Sub-district Traditional Market of Penajam Paser Utara Regency is 22.60% and the rest of 77.40% is explained by other variables or factors outside the variables X1, X2, X3, and X4. The price has a dominant effect on the decision to buy. This is indicated by the beta value coefficient value variable 0.284 greater than 0.209 distribution variables, 0.176 products and the lowest is a promotion of 0.026. This means that the better the price offered in accordance with the quality then affects the decision to purchase rice to consumers. Key word :  Mix, Rice, Local, Traditional market